Unified communications forensics anatomy of common UC attacks - Grant, Nicholas, 1978-; Shaw, Joseph W. II 1976- (Syngress is an imprint of Elsevier, 2013)
Explains the issues, vulnerabilities, and demonstrate the attacks, forensic artifacts, and countermeasures required to establish a secure Unified Communications environment. This book provides material found on the market, including analysis of forensic artifacts in common Unified Communication attacks